The Relationship between Verniks Caseosa with C-Reaktif Protein (CRP) Levels and Premature Infant Wellness - Setiawandari Setiawandari; Tetty Rihardini; Siswati Siswati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Premature infants are still the leading cause of infant mortality in Indonesia. This is because premature babies are a risk of infections and other congenital complications. Premature babies tend to have less vernix caseosa due to vernix caseosa production as well as surfactant production, i.e. at 21 weeks of gestation and the older the gestational age the more vernix caseosa is most produced. The purpose of this study was to determine the relationship between vernix caseosa and increased C-Reactive Protein (CRP) levels toward well-being in premature infants. Using terminology design not the type of research is analytical using a perspective cohort design. The research subjects treated in the NICU room at Putri Surabaya Hospital in the period January to November 2021 were preterm infants between 0 and 1 month of age, and premature infants with few vernix caseosa. Inclusion criteria were premature infants 0-1 months of age, gestational age less than 38 weeks, birth weight 1500-2500 grams, a preterm newborn with vernix caseosa, and little or without vernix caseosa. While the exclusion criteria were preterm newborns with congenital complications and abnormalities. The data were analyzed using chi-square test and Pearson correlation bimodal analysis. The results showed a relationship between vernix caseosa and CRP levels in premature infants = 0.014, and vernix caseosa and wellness conditions in premature infants = 0.030, but no relationship between CRP levels and premature wellness. children = 0.222. The conclusion is that the more Vernix Caseosa in premature babies, the lower the CRP levels and the condition in which premature babies become more agile.